Daily very low UV dose exposure enhances adaptive immunity, compared with a single high‐dose exposure. Consequences for the control of a skin infection - Cela, Eliana Maiten (2018)
Ultraviolet radiation (UVr) promotes several well‐known molecular changes, which may ultimately impact on health. Some of these effects are detrimental, like inflammation, carcinogenesis and immunosuppression. On the other hand, UVr also promotes vitamin D synthesis and other beneficial effects. We recently demonstrated that exposure to very low doses of UVr on four consecutive days [repetitive low UVd (rlUVd)] does not promote an inflammatory state, nor the recruitment of neutrophils or lymphocytes, as the exposure to a single high UV dose (shUVd) does. Moreover, rlUVd reinforce the epithelium by increasing antimicrobial peptides transcription and epidermal thickness. The aim of this study was to evaluate the adaptive immune response after shUVd and rlUVd, determining T‐cell and B‐cell responses. Finally, we challenged animals exposed to both irradiation procedures with Staphylococcus aureus to study the overall effects of both innate and adaptive immunity during a cutaneous infection. We observed, as expected, a marked suppression of T‐cell and B‐cell responses after exposure to an shUVd but a novel and significant increase in both specific responses after exposure to rlUVd. However, the control of the cutaneous S. aureus infection was defective in this last group, suggesting that responses against pathogens cannot be ruled out from isolated stimuli.